The impact of QR code implementation on the level of satisfaction among restaurant customers / Nurliyana Abas, Hanani Hussin and Dr. Law Kuan Kheng - Abas, Nurliyana; Hussin, Hanani; Law, Kuan Kheng (Universiti Teknologi MARA, Kedah, 2024)
The introduction of new technologies and innovations aimed at enhancing the customer experience has caused significant changes in the restaurant industry in recent years. Quick response codes, or QR codes, are one such technology that is becoming more and more common in the restaurant business (Ozturkcan & Kitapci, 2023). QR codes are twodimensional barcodes that can be scanned using a smartphone camera, providing customers with access to a range of information. This includes menus, promotions, and payment options. Restaurants can save money and resources by using QR code menus instead of paper menus, which can be printed, updated, and discarded. QR codes are becoming more and more common in the restaurant industry. Furthermore, implementing QR codes in restaurants has significantly impacted customer satisfaction (Hossain et al., 2018). In addition, QR codes have been discovered to improve service operations, increase efficiency, and reduce costs (Intal et al., 2020). According to a study on the implementation of a Restaurant Information System (RIS) with QR codes to improve service operations in casual fine dining restaurants, the primary attributes of implementing Mobile Food Ordering Applications (MFOAs) included information, system, and service quality, as well as product quality (Intal et al., 2020). Malaysia witnessed a growth in the number of QR code users, reaching 338,700 in July 2023. The country also saw a rapid increase in the use of QR payments during April and May 2020, with an addition of 118,000 new users (Iris, 2023). The research gap in the existing literature on the impact of QR code implementation in restaurants on customer satisfaction lies in the need to address this relationship specifically within the context of the restaurant industry. Several studies have examined the impact of QR codes on customer satisfaction in general or in the online domain (Hossain et al., 2018). However, there is a lack of comprehensive research that focuses on the unique setting of restaurants and the direct influence of QR code implementation on the level of satisfaction among restaurant customers. Furthermore, existing literature has primarily emphasized the benefits of QR code technology in terms of efficiency, cost reduction, and revenue increase. Nevertheless, it is necessary to delve deeper into its direct impact on customer satisfaction within the restaurant environment. This conceptual paper explores the impact of QR code implementation on satisfaction among restaurant customers. Hence, by examining how customers perceive the usefulness, usability, and acceptability of QR codes, we can gain insights into how this technology affects customer satisfaction.